Capital Structure, Profitability, and Firm Value - Akhmadi Akhmadi; Ana Susi Mulyani; Nauval Noviansyah (Jurnal Riset Akuntansi Terpadu, 2022)
The purpose of this study was to determine the effect of capital structure on firm value, either directly or indirectly. The population in this study are all wholesale companies listed on the Indonesia Stock Exchange (IDX) 2009-2018. While the sample is 22 companies which are determined by using the judgment sampling method. The research design uses a causality design. Data analysis used descriptive statistics, and inferential statistics included classical assumption tests, partial hypothesis tests and mediation tests. The results of the study prove that capital structure has no significant positive effect on firm value. Profitability can mediate the effect of capital structure on firm value.